Literary literacy practices with Cordel Literature: dialogic propositions from the textbook (Olhar de Professor, 2024)
For many years, cordel literature has been a vehicle for exploring historical and cultural issues in the Northeast in teaching practices, especially in the early grades of elementary school. Consequently, this approach to reading and producing literary texts can be a prerequisite for literary literacy practices that are coherent with the linguistic-discursive and social needs of the subjects, an issue that can affect teaching work in different ways, including through textbook guidelines. In view of this, the aim of this study is to analyze literary literacy practices with cordel literature in activities from the textbook "A conquista da Língua Portuguesa" for the 3rd year of elementary school, based on Dialogic Discourse Analysis. Methodologically, this is a qualitative documentary study. The results indicate the use of narratives as a pretext for observing formal aspects of the language, as well as the fact that these are texts produced exclusively for the material/textbook analyzed, and that these narratives are poor in terms of possibilities for the process of training literary readers.
Keywords: Literary Literacy; Cordel Literature; Teaching